Assessing Direct and Indirect Economic Impacts of a Flood Event Through the Integration of Spatial and Computable General Equilibrium Modelling - Lorenzo Carrera; Gabriele Standardi; Francesco Bosello; Jaroslav Mysiak (Fondazione Eni Enrico Mattei (FEEM), 2014)
In this paper we developed and tested an integrated methodology for assessing direct and indirect economic impacts of flooding. The methodology combines a spatial analysis of damage to physical stocks with a general economic equilibrium approach using a regionally-calibrated (to Italy) version of a Computable General Equilibrium (CGE) global model. We applied the model to the 2000 Po river flood. To account for the uncertainty in the induced effects on regional economies, we explored three disruption and two recovery scenarios. The results prove that: i) indirect losses are a significant share of direct losses, and ii) the model is able to capture both positive and negative economic effects of a disaster in different areas of the same country. The assessment of indirect impacts is essential for a full understanding of the economic outcomes of natural disasters.
Keywords: Q5; Q54; 330; Flood Risk; Indirect Impacts; Computable General Equilibrium; Natural Disasters